Survival and Neurodevelopmental Outcomes Among Periviable Infants. Issue 3 (September 2017) - Younge, N.; Goldstein, R.F.; Bann, C.M.; Hintz, S.R.; Patel, R.M.; Smith, P.B.; Bell, E.F.; Rysavy, M.A.; Duncan, A.F.; Vohr, B.R.; Das, A.; Goldberg, R.N.; et al.
Abstract : ( N Engl J Med . 2017;376(7):617–628) Care of periviable infants remains a great challenge in neonatal and perinatal medicine. Although data from the past 5 years indicate that mortality has declined among periviable infants, little is known about the relationship between survival and neurodevelopmental outcomes. The authors of the present study thus evaluated changes over time in survival and neurodevelopmental outcomes among infants born at 22 to 24 weeks of gestation, as assessed at 18 to 22 months of corrected age.